A case study on Rural Marketing Strategies of MNCs using 6E framework in India and Indonesia - Dr. Alka Maurya (AIBPM Publisher, 2019)
Multinational Companies in a bid to increase their revenue and profit are now eyeing the emerging markets. Considering the saturation in the urban market they are now targeting the consumers in rural markets of emerging economies. Lowering price by reducing the volume, customization, mass production are the strategies of the past, these companies have now come up with innovative strategies wherein they involve the rural population so that they help them in reaching to the customers in the remotest part of the country. This case study is an attempt to study the strategies used by the companies to reach the rural population and arrive at a framework used by the companies in India and Indonesia. The information is collected from the secondary sources to compile and analyze the strategies of leading MNCs to increasing their share in the emerging economies.